The Effectiveness of Eye Movement Desensitization and Reprocessing Therapy to Treat Symptoms Following Trauma in Timor Leste. Issue 2 (2nd March 2016) - Schubert, Sarah J.; Lee, Christopher W.; de Araujo, Guilhermina; Butler, Susan R.; Taylor, Graham; Drummond, Peter D.
Abstract: The effectiveness of eye movement desensitization and reprocessing (EMDR) therapy for treating trauma symptoms was examined in a postwar/conflict, developing nation, Timor Leste. Participants were 21 Timorese adults with symptoms of posttraumatic stress disorder (PTSD), assessed as those who scored ≥2 on the Harvard Trauma Questionnaire (HTQ). Participants were treated with EMDR therapy. Depression and anxiety symptoms were assessed using the Hopkins Symptom Checklist. Symptom changes post‐EMDR treatment were compared to a stabilization control intervention period in which participants served as their own waitlist control. Sessions were 60–90 mins. The average number of sessions was 4.15 ( SD = 2.06). Despite difficulties providing treatment cross‐culturally (i.e., language barriers), EMDR therapy was followed by significant and large reductions in trauma symptoms (Cohen's d = 2.48), depression ( d = 2.09), and anxiety ( d = 1.77). At posttreatment, 20 (95.2%) participants scored below the HTQ PTSD cutoff of 2. Reliable reductions in trauma symptoms were reported by 18 participants (85.7%) posttreatment and 16 (76.2%) at 3‐month follow‐up. Symptoms did not improve during the control period. Findings support the use of EMDR therapy for treatment of adults with PTSD in a cross‐cultural, postwar/conflict setting, and suggest that structured trauma treatments can be applied in Timor Leste.